MARKET REGIME AND RELATIVE RISK BETWEEN SECTORS - Defrizal DEFRIZAL (International Conference On Law, Business and Governance (ICon-LBG), 2016)
This study aims to explain the occurrence of market regime and the measurement of the relative risk between sectors in stocks of financial sector and stocks of trade sector in the Indonesia Stock Exchange. This study uses Markov regime switching model, to identify market regime that occurred in the financial sector and the trade sector. Then the model parameters using the Variation Coefficient be measured relative risk of each sector of the market that occurred regime. This study uses data Indonesian stock exchange for the observation period January 1996 until March 2016. The results of this study indicate that market regime that occurred in the financial sector and the trade sector is divided into bullish regime and bearish regime, where the difference is primarily due to differences in volatility. The risk per unit of return indicate that relativelystocks of trade sectors had a higher risk than stocks of financial sector in Indonesia Stock Exchange.